Contextual Analysis of the Works of Four selected Contemporary African Artists - Sobowale, Tolulope Oladimeji; Adeloye, Adebayo Abiodun; Odewole, Peter Oluwagbenga; Afolabi, Benjamin Eni-Itan F.; Adepegba, Kehinde (NIU Journal of Humanities, 2023)
The study is focused on four purposively selected contemporary African artists and their works. Their selection is inspired by the expressive content embedded in their selected works. Primary and secondary method was used in data collection and the data obtained is analyzed using descriptive approach. While historical analysis including biographical, formal, and contextual analytical methods is employed in bring to fore the contributions of their artworks in ensuring peoples wellbeing in the society. Key w ords: Contemporary, African Artists, Expressive Context, Painting, Metal Sculpture.